2013
DOI: 10.1371/journal.pone.0071660
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation Promotes Wound Healing by Enhancing Dermal Fibroblast Activity and Promoting Myofibroblast Transdifferentiation

Abstract: Electrical stimulation (ES) has long been used as an alternative clinical treatment and an effective approach to modulate cellular behaviours. In this work we investigated the effects of ES on human skin fibroblast activity, myofibroblast transdifferentiation and the consequence on wound healing. Normal human fibroblasts were seeded on heparin-bioactivated PPy/PLLA conductive membranes, cultured for 24 h, and then exposed to ES of 50 or 200 mV/mm for 2, 4, or 6 h. Following ES, the cells were either subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(145 citation statements)
references
References 67 publications
(70 reference statements)
4
124
0
8
Order By: Relevance
“…JNK is a key factor in TGF-β1-stimulated lung fibrosis [29]. Inhibition of JNK, ERK and p38 can partially reverse TGF-β1-induced epithelial-tomesenchymal transition (EMT) and fibrosis [5,30]. We are interested in knowing whether MAPK plays a role in the inhibitory effects of LB on scar formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JNK is a key factor in TGF-β1-stimulated lung fibrosis [29]. Inhibition of JNK, ERK and p38 can partially reverse TGF-β1-induced epithelial-tomesenchymal transition (EMT) and fibrosis [5,30]. We are interested in knowing whether MAPK plays a role in the inhibitory effects of LB on scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…(b) Western blotting showed that LB significantly reduced the phosphorylation of ERK that was induced by TGF-β1. Then, fibroblasts were divided into six groups and treated with TGF-β1 (5 ng/mL), LB (25 μg/mL), TGF-β1 (5 ng/mL) + LB (25 μg/mL), TGF-β1 (5 ng/mL) + PD98059 (30 …”
Section: Lb Inhibited the Contraction Of Tgf-β1-stimulated Fibroblastmentioning
confidence: 99%
“…1B and C). CAFs, characterized also by their expression of aSMA, are known to be similar to myofibroblasts that are active in wound repair, where their coordinated motility and contraction is crucial in the process of wound closure (23)(24)(25). We therefore performed an in vitro wound closure assay to test the activation of NMFs by tumor cell-secreted factors.…”
Section: Paracrine Signaling From Breast Tumor Cells Reprograms Mammamentioning
confidence: 99%
“…LDHB Western blotting in TCLs served as a loading control. To check for cell leakiness, we measured medium LDH activity using a cytotoxicity kit (19,20). As shown in the bar graph in Fig.…”
Section: Anti-jo-1 Autoantibodies React Mainly With Whep and Abd Domamentioning
confidence: 99%